A model to explain suicide by self-immolation among Iranian women: A grounded theory study. Issue 7 (November 2015) - Khankeh, Hamid Reza; Hosseini, Seyed Ali; Rezaie, Leeba; Shakeri, Jalal; Schwebel, David C.
Highlights We present a grounded theory study exploring suicide by self-immolation in Iran. A conceptual model explains relations among motives for self-immolation attempts. Family conflicts are pivotal risk factors and should be addressed in interventions. Mental health influences the self-immolation process at multiple levels.